Kimboza, a Small Lowland Forest With an Outstanding Herpetofauna Diversity in East Africa - John V. Lyakurwa; Simon P. Loader; Wilirk Ngalason; Rikki Gumbs; Caleb Ofori‐Boateng; H. Christoph Liedtke (Ecology and Evolution)
ABSTRACT The Eastern Arc Mountains (EAM) and Coastal forests of Tanzania are renowned for harboring large number of threatened and endemic vertebrate species, yet most of these areas have been partially studied. The Kimboza Nature Forest Reserve (KNFR) is a small forest which is in transition between the EAM and Coastal forests, and among the poorly surveyed areas for amphibians and reptiles. We conducted systematic surveys across the KNFR in 2012 and between 2020 and 2023 using a range of approaches with the aim of establishing a comprehensive and updated list of reptile and amphibian species and assess the contribution of EAM and Coastal forests to the KNFR's herpetofauna. We identified 77 species, 29 amphibians and 48 reptiles, substantially updating previous species lists. Three of these species (Kinyongia magomberae, Trachylepis boulengeri and Philothamnus macrops) represent range extensions from previously known ranges. Fourteen species are endemic to East Africa, 11 of them being restricted to Tanzania. These results make the KNFR the richest forest reserve for herpetofauna per square km in Tanzania, and most similar in its composition to the Coastal, rather than Eastern Arc forests. With the caveats concerning taxonomic uncertainties and the inequalities of sampling intensity across the region, this study shows that the KNFR is an important area that deserves conservation attention. The KNFR, like other Coastal forests, is under significant pressure from anthropogenic activities which call for an urgent action to protect this small but rich forest.